2019
DOI: 10.3390/ijms20225661
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Gut-on-a-Chip Model for High Throughput Disease Modeling and Drug Discovery

Abstract: A common bottleneck in any drug development process is finding sufficiently accurate models that capture key aspects of disease development and progression. Conventional drug screening models often rely on simple 2D culture systems that fail to recapitulate the complexity of the organ situation. In this study, we show the application of a robust high throughput 3D gut-on-a-chip model for investigating hallmarks of inflammatory bowel disease (IBD). Using the OrganoPlate platform, we subjected enterocyte-like ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 65 publications
1
110
0
Order By: Relevance
“…They used the device to test the metabolic capacity of verapamil and isofluamide, and the results showed that intestinal cells had high levels of CYP450 enzyme expression, which enhanced the metabolism of oral drugs. Claudia et al constructed a high-throughput intestinal chip device to mimic inflammatory bowel disease (IBD) in vitro ( Figure 5A) [122]. Inhibition of crucial inflammation regulators RELA and MYD88 by on-chip adenovirus short hairpin RNA (shRNA) transduction can reduce the IBD phenotype by reducing cytokine production.…”
Section: Gut-on-a-chipmentioning
confidence: 99%
See 1 more Smart Citation
“…They used the device to test the metabolic capacity of verapamil and isofluamide, and the results showed that intestinal cells had high levels of CYP450 enzyme expression, which enhanced the metabolism of oral drugs. Claudia et al constructed a high-throughput intestinal chip device to mimic inflammatory bowel disease (IBD) in vitro ( Figure 5A) [122]. Inhibition of crucial inflammation regulators RELA and MYD88 by on-chip adenovirus short hairpin RNA (shRNA) transduction can reduce the IBD phenotype by reducing cytokine production.…”
Section: Gut-on-a-chipmentioning
confidence: 99%
“…Some other-organ-on-a-chip systems for drug toxicity testing. (A) Schematic representation of the 3-lane OrganoPlate gut-on-a-chip model[122]. (B) A microengineered model of human pulmonary edema[127].…”
mentioning
confidence: 99%
“…In-vitro models that closely mimic the human intestinal epithelium and its physiology are important tools for drug development processes [ 1 , 2 , 3 ]. As oral drug delivery is the preferred route of administration [ 4 ], such models have enormous potential to improve and speed up studies of absorption [ 5 ], disease modelling [ 6 ], drug metabolism and interactions as well as associated toxicity [ 7 , 8 ]. Therefore, patient-specific absorption models that take the gut complexity, passive and active transport and patient variability into consideration could be highly valuable in the evaluation of candidate drugs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adoption of new techniques in the drug discovery pipeline has been regarded as a solution to this serious issue. Typically, artificial intelligence [1], cell spheroid model [2], organ-on-a-chip [3], organoid [4], 3D bioprinting [5], and similar techniques have been gradually merged into the pharmaceutical industry to increase the efficiency of drug discovery. Among them, the 3D bioprinting technique offers highly biomimetic in vitro models and has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%